Copy number variation in patients with cervical artery dissection - Grond-Ginsbach, Caspar; Pjontek, Rastislav; Wiest, Tina; Burwinkel, Barbara; Kloss, Manja; Arnold, Marie-Luise; Lichy, Christoph; Haußer-Siller, Ingrid (European journal of human genetics, 2012)
Cervical artery dissection (CeAD) occurs in healthy young individuals and often entails ischemic stroke. Skin biopsies from most CeAD-patients show minor connective tissue alterations. We search for rare genetic deletions and duplication that may predispose to CeAD. Forty-nine non-traumatic CeAD-patients with electron microscopic (EM) alterations of their dermal connective tissue (EM+ patients) and 21 patients with normal connective tissue in skin biopsies (EM− patients) were analyzed. Affymetrix 6.0 microarrays (Affymetrix) from all patients were screened for copy number variants (CNVs). CNVs absent from 403 control subjects and from 2402 published disease-free individuals were considered as CeAD-associated. The genetic content of undentified CNVs was analyzed by means of the Gene Ontology (GO) Term Mapper to detect associations with biological processes. In 49 EM+ patients we identified 13 CeAD-associated CNVs harboring 83 protein-coding genes. In 21 EM− patients we found five CeAD-associated CNVs containing only nine genes (comparison of CNV gene density between the groups: Mann-Whitney P=0.039). Patients’ CNVs were enriched for genes involved in extracellular matrix organization (COL5A2, COL3A1, SNTA1, P=0.035), collagen fibril organization COL5A2, COL3A1, (P=0.0001) and possibly for genes involved in transforming growth factor beta (TGF)-beta receptor signaling pathway (COL3A1, DUPS22, P=0.068). We conclude that rare genetic variants may contribute to the pathogenesis of CeAD, in particular in patients with a microscopic connective tissue phenotype.